Antimicrobial Lipids from Plants and Marine Organisms: An Overview of the Current State-of-the-Art and Future Prospects - Eliana Alves; Marina Dias; Diana Lopes; Adelaide Almeida; Maria do Rosário Domingues; Felisa Rey (MDPI AG, 2020)
In the actual post-antibiotic era, novel ways of rethinking antimicrobial research approaches are more urgent than ever. Natural compounds with antimicrobial activity such as fatty acids and monoacylglycerols have been investigated for decades. Additionally, the interest in other lipid classes as antimicrobial agents is rising. This review provides an overview on the research about plant and marine lipids with potential antimicrobial activity, the methods for obtaining and analyzing these compounds, with emphasis on lipidomics, and future perspectives for bioprospection and applications for antimicrobial lipids. Lipid extracts or lipids isolated from higher plants, algae or marine invertebrates are promising molecules to inactivate a wide spectrum of microorganisms. These lipids include a variety of chemical structures. Present and future challenges in the research of antimicrobial lipids from natural origin are related to the investment and optimization of the analytical workflow based on lipidomics tools, complementary to the bioassay-guided fractionation, to identify the active compound(s). Also, further work is needed regarding the study of their mechanism of action, the structure-activity relationship, the synergistic effect with conventional antibiotics, and the eventual development of resistance to lipids, which, as far as is known, is unlikely.